The effect of orally administered metoprolol on the frequency and severity of rocuronium injection pain - Şen, Özlem; Kalaycı, Dilek; Kabaosman, Tülay; Kaya, Menşure; Yılmaz, Seda (The European Research Journal, 2023)
Objectives: This study aimed to examine the effects of orally administered metoprolol on the frequency and severity of pain caused by rocuronium injection in patients who started to use and were currently using oral metoprolol for any reason such as ischemic heart disease, hypertension, and arrhythmias. Methods: Patients were evaluated in four groups. Group M: patients currently using metoprolol and who did not receive lidocaine before the application of rocuronium. Group ML: patients currently using metoprolol and who received lidocaine before rocuronium application. Group L: patients currently not using metoprolol and received lidocaine before rocuronium application. Group C: patients currently not using metoprolol and who did not receive lidocaine before rocuronium application. Following the induction of general anesthesia with thiopental sodium, a researcher blind to the groups observed the pain during rocuronium injection based on the following scale: (1) no reaction, (2) movement only in the ankle, (3) movement or withdrawal only in the arm (shoulder and ankle), and (4) diffuse reaction (movement or withdrawal in more than one extremity, coughing and holding breath). Results: Two hundred patients with 50 in each of four groups were included. The incidence of pain was statistically significantly lower in Group ML compared to Groups M and C (p = 0.001). The correlations between pain caused by rocuronium injection and duration of metoprolol usage and the time since the last dose were not statistically significant (for all, p > 0.05). Conclusions: Oral metoprolol combined with lidocaine reduced pain and withdrawal reflex caused by rocuronium injection. No significant difference was observed between the last dose and the duration of metoprolol usage.